2004
DOI: 10.1023/b:joih.0000030226.59785.38
|View full text |Cite
|
Sign up to set email alerts
|

Health in Relation to Unemployment and Sick Leave Among Immigrants in Sweden from a Gender Perspective

Abstract: The purpose of this study was to analyze health in relation to unemployment and sick leave among immigrants from a gender perspective. Questionnaire, observations, and group discussions were used for data collection. The study group consisted of 60 unemployed persons with immigrant or refugee background, 30 women and 30 men. Slightly more than half of the participants considered their health to be poor and experienced physical and/or mental disorders. The female participants in comparison to male participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 10 publications
3
28
1
3
Order By: Relevance
“…We are conscious, as Akhavan and her colleagues have pointed out (3), that identifying or monitoring minority groups can lend itself easily to stigmatization if not properly handled. The usefulness of terms such as immigrant or foreign worker is their capacity as descriptors of power imbalances, social stratification, and the lesser power that minority groups often have in societies (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are conscious, as Akhavan and her colleagues have pointed out (3), that identifying or monitoring minority groups can lend itself easily to stigmatization if not properly handled. The usefulness of terms such as immigrant or foreign worker is their capacity as descriptors of power imbalances, social stratification, and the lesser power that minority groups often have in societies (3).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study of unemployment and sick leave in Sweden (3) found that more than half of the immigrant study participants considered their health to be poor, and they experienced various physical and mental health disorders. Many of the participants actually attributed their poor health to their unemployment status.…”
Section: Importance Of Workmentioning
confidence: 99%
“…However, no studies to date have analyzed sick leave among immigrants living in Spain, and only a few have concerned sick leave among immigrants in Europe (9)(10)(11)(12).…”
Section: Soler-gonzález Et Almentioning
confidence: 99%
“…Swedish studies reveal that immigrant women experienced discrimination in the labour market and were mainly employed as cleaners, home-helpers or nursery assistants (Akhavan et al, 2007(Akhavan et al, , 2004. As a parallel, immigrants in Canada and Scandinavia, most of which are from low-and middle-income countries, often experience social exclusion and discrimination because of their race, language, religion and immigrant-status.…”
Section: Introductionmentioning
confidence: 99%